Challenges and opportunities in the digital era : 17th IFIP WG 6.11 Conference on e-Business, e-Services, and e-Society, I3E 2018, Kuwait City, Kuwait, October 30-November 1, 2018, Proceedings /: 17th IFIP WG 6.11 Conference on e-Business, e-Services, and e-Society, I3E 2018, Kuwait City, Kuwait, October 30-November 1, 2018, Proceedings. (2018) - Unknown
No abstract available